Cloning and sequence of the human adrenodoxin reductase gene. - Lin, D (1990)
Adrenodoxin reductase (ferrodoxin:NADP+ oxidoreductase, EC 1.18.1.2) is a flavoprotein mediating electron transport to all mitochondrial forms of cytochrome P450. We cloned the human adrenodoxin reductase gene and characterized it by restriction endonuclease mapping and DNA sequencing. The entire gene is approximately 12 kilobases long and consists of 12 exons. The first exon encodes the first 26 of the 32 amino acids of the signal peptide, and the second exon encodes the remainder of signal peptide and the apparent FAD binding site. The remaining 10 exons are clustered in a region of only 4.3 kilobases, separated from the first two exons by a large intron of about 5.6 kilobases. Two forms of human adrenodoxin reductase mRNA, differing by the presence or absence of 18 bases in the middle of the sequence, arise from alternate splicing at the 5' end of exon 7. This alternately spliced region is directly adjacent to the NADPH binding site, which is entirely contained in exon 6. The immediate 5' flanking region lacks TATA and CAAT boxes; however, this region is rich in G + C and contains six copies of the sequence GGGCGGG, resembling promoter sequences of "housekeeping" genes. RNase protection experiments show that transcription is initiated from multiple sites in the 5' flanking region, located about 21-91 base pairs upstream from the AUG translational initiation codon.